Unified First Order Inertial Element Based Model of Magnetostrictive Hysteresis and Lift-Off Phenomenon - Szewczyk, Roman (Materials (Basel), 2019)
The present paper presents a new model of magnetostrictive hysteresis loop. A unified approach of both the hysteresis of λ(B) relation, as well as the lift-off phenomenon is proposed, which are explained together on the base of the response of the first order inertial element. Considering previously presented reports, the Maxwell–Boltzmann distribution based model of magnetostrictive characteristics with local maxima, enables modeling magnetostrictive loops. The model was validated on the results of measurements of magnetostrictive hysteresis loops of Mn(0.70)Zn(0).(24)Fe(2.06)O(4) ferrite for power applications. Good agreement was confirmed for major magnetostrictive loop, especially for smaller values of flux density. As a result, the proposed model may be used for modeling the magnetostrictive response of inductive components of electrical machines, power conversion devices or magnetostrictive actuators.